Pengaruh Minat Siswa pada Pembelajaran Biologi Terhadap Hasil Belajar Siswa SMA N 1 Beringin: (The Effect Of Student Interest In Biology Learning On Student Learning Outcomes Of SMA N 1 Beringin) - Ananda Putri Ananda Putri; Agus Wahyuda; Siti Humayroh; Reni Rahayu Reni Rahayu; Azzahra Putri Ramadana Azzahra Putri Ramadana (BIODIK, 2023)
The aim of this study is to investigate the effect of students' interest in biology on academic performance. This study was conducted at SMA N 1 Beringjin in 2022. This type of survey is a sample survey of 90 students in the 11th MIPA class. The research tool was a Google Forms questionnaire with 30 questions, administered to students. The indicators of the survey are the pleasure, interest, interest and participation of students in biology. The data analysis was performed by calculating the survey score of each student, applying it to the presentation and interpreting it into categories of good, good, bad and poor. As a result, the students 'pleasure was 77.9%, the students' interest was 77.1%, the students 'interest was 76.1% and the students' participation was 75.9%. Following this study, it was found that students 'interest in learning had a positive effect on students' school results, and the average level of interest in biological research in Beringin Class XI SMAN 1 in 2022 was 76.75, a very good category, seemed to correspond with expected. Key words: Interest, Biology Learning, Learning Outcome Â  ABSTRAK Tujuan dari penelitian ini adalah untuk mengetahui pengaruh minat siswa pada biologi terhadap prestasi akademik. Penelitian ini dilakukan di SMA N 1 Beringjin pada tahun 2022. Jenis survei ini adalah sampel survei terhadap 90 siswa kelas XI MIPA. Alat penelitian adalah kuesioner Google Forms dengan 30 pertanyaan, diberikan kepada siswa. Indikator survei adalah kesenangan, minat, minat dan partisipasi siswa dalam biologi. Analisis data dilakukan dengan menghitung skor survei masing-masing siswa, menerapkannya pada presentasi dan menginterpretasikannya ke dalam kategori baik, baik, buruk dan buruk. Hasilnya, kesenangan siswa sebesar 77,9%, minat siswa sebesar 77,1%, minat siswa sebesar 76,1% dan partisipasi siswa sebesar 75,9%. Berdasarkan penelitian ini diketahui bahwa minat belajar siswa berpengaruh positif terhadap hasil belajar siswa, dan rata-rata tingkat minat penelitian biologi pada siswa kelas XI SMAN 1 Beringin tahun 2022 adalah 76,75 dengan kategori sangat baik, tampaknya sesuai dengan yang diharapkan. Kata kunci: Minat, Pembelajaran Biologi, Hasil Belajar